The empathic response: analysis of the consistency of performance in the different steps of the process - Reyes Figueroac, Gabriel; Benitez J., Dagoberto; Ortíz de Zúñiga y E., Blanca (Revista de Psicología, 1994)
On the assumption of the existence of a series of sequential steps as part of the empathic response production process, the present study tried to obtain information about the possible relationship between said steps. With the use of an "ex-post-facto" type design, and from the comparison of two groups with different levels of empathic acuity, the degree of consistency in the performance before each of these steps was examined. It is concluded that although a medium or high performance in the steps considered as previous, the response does not ensure obtaining high levels of Empathic Acuity, however these same levels are necessary for the successful achievement of the terminal response.